Condition and Level Utilization Facilities of Kronjo Fish Landing Place Tangerang Regency Banten Province - Devi Pujiastuti; Ririn Irnawati; Ani Rahmawati (JURNAL PERIKANAN DAN KELAUTAN, 2018)
Kronjo Sub-district was established to be one of the main areas of Tangerang Regency Minapolitan. Minapolitan area is a development concept based on economic management of the region with the motor of marine and fisheries sector, based on the principle of integration, efficiency, quality and acceleration. The purpose of this study was to identify the condition and to analyze the level of facility utilization of Kronjo Fishing Port. This research was conducted in July-November 2017. The method used in this research is survey. The depth of the harbor pool, the need for clean water, the need for ice beams, and the fishing port area of Kronjo Fishing Port has exceeded its capacity, with the level of facility utilization 223,33%, 2.111,09%, 702%, 200%-400%. Where the depth of the harbor pool is3.5 m and it is only available 2 m and has a shallowing to 1.85 m. Clean water available in Kronjo Fishing Port is only 550 L/day while the need for clean water is 11,611 L/day, needs of ice beam 70.2 tons and available in Kronjo Fishing Port only 10 tons. The total area of facilities of Kronjo Fishing Port 681.8 m2and the minimum land area of Kronjo Fishing Port required is 1,363.6 m2 and the maximum land area required is 2,727.2 m2.